Anisotropy and inter-condyle heterogeneity of cartilage under large-strain shear. (8th February 2017) - Santos, Stephany; Maier, Franz; Pierce, David M.
Abstract: We were the first to examine the mechanical responses of skeletally mature bovine femoral cartilage under large-strain simple shear (up to ±20%) using a multiaxial shear testing device. Since shear loading is critical in both tissue failure and chondrocyte responses, we aimed to probe (1) anisotropy with respect to the split-line direction (principal alignment of the collagen fibers near the articulating surface), (2) heterogeneity between femoral condyles, and (3) the influence of local cartilage thickness. We harvested a total of 48 cuboid cartilage specimens from four bovine knee joints. With each specimen we applied shear strains both parallel and perpendicular to the local split-line direction at a rate of 75 μm/min and calculated the peak-to-peak shear stresses, shear strain–energy dissipation densities, and peak effective shear moduli. The Wilcoxon signed rank test revealed that the medial condyle was anisotropic in some mechanical measures at applied shear strains above 5%, while the lateral condyle was mechanically isotropic at all applied shear strains. The Kruskal–Wallis test revealed no significant differences in the median mechanical behavior of the lateral and medial condyles. Spearman׳s rank correlations revealed statistically significant negative monotonic correlations among thickness and most of our mechanical measures for both lateral and medial condyles at most applied strains and directions of applied shear. These results suggest that large-strain analyses account for nonlinear, anisotropic and location-dependent effects not fully realized at small strains. Our findings may inspire new experiments and models that consider anisotropy and heterogeneity of cartilage in ways previously ignored.